Legal Barriers in Developing Educational Technology - Tran, Cam Ai; Nguyen, Truc Thanh Lam (Vietnam Journal of Education, 2025)
The integration of technology in education has transformed teaching and learning, making digital tools essential in the context of Industry 4.0. However, the rapid evolution of educational technology poses significant legal challenges that must be addressed for effective implementation. This article examines the main legal barriers to adopting educational technologies in Vietnam, specifically focusing on data privacy, intellectual property concerns, and compliance with educational standards. Through a comparative legal analysis of domestic and international laws, the study sheds light on the legal frameworks affecting technology integration in education. Data privacy issues arise from the sensitive information collected in educational settings, while intellectual property challenges relate to protecting and fairly using digital content and software. Additionally, compliance with educational standards is crucial for ensuring the quality of these technologies. The findings highlight the legal obstacles hindering educational technology growth in Vietnam and propose strategies to overcome them, such as enhancing data privacy laws, strengthening intellectual property rights, updating educational standards, and fostering public-private partnerships. This research study aims to support policymakers and educational institutions in creating robust legal frameworks that encourage innovation while ensuring regulatory compliance, ultimately improving the quality of education and preparing students for a digital economy.